(3ZGjI GdSQhQ aj TQM GdTPhQs - (3Ydj Hf eMeO Hf CjOeQ GdpLrdnOcj, YR GdOjf,J (B742 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eGdc Gdedc Gdedc GdMb GdbOjQ GdZahQ CeG HYO aEf GdGfSGf YbO YgO hdGjI HGdNdGaI hGdJecjf aj gPg GdOGQ hbO hbaJ Ydi OjhGf HgGA GdOjf s
(3BNQgG (B:s
(3ef BNQ GdehLhO jJTeY cTeYjI GdChd haj gPg GdefRdI jSQY Gdjg GdJTjY dCf GdLSO GdeTeY bO UGQ dg s
(3HgG fXGe GdJYbjHIs
(3hgh KdGKI GLRGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B28s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdcjejGA h GdWHjYjGJs